STRATEGI PENGEMBANGAN USAHA AGROINDUSTRI KOPI LUWAK PADA SATRIA AGROWISATA DI KABUPATEN GIANYAR - Rosyanta, Putu Marita Cakatini; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This study aims to analyze the internal and external conditions as well as compose and recommend the business development strategy of agro-industries of Civet coffee at Satria agro- tourism in the Gianyar Regency. The methods used in this research is a method of observation field and in-depth interviews using questionnaire. Data field observations and interviews are then analyzed to obtain formulation strategies using the SWOT analysis. The assessment weighting and rating conducted by 5 experts. Results of the study show that there are 5 strengths, 5 weaknesses, 4 opportunities, and 3 threats. Results weighting and rating values for the matrix that the weighted Internal Factor Evaluation (IFE) was 3.72 and matrix External Factor Evaluation (EFE) is 3.75. This value indicates a strong position on the matrix Internal external (IE) and the strategy to do is intensive and integrative strategies. Based on SWOT Matrix Analysis, priority alternative strategy is maintaining of price and quality to expand marketing. Keywords : strategy, SWOT, agro tourism, civet coffee, QSPM